Relação entre eficiência e rentabilidade em instituições financeiras bancárias no Brasil - Mendonça, Douglas José (2017)
The aim of this research was to investigate the relationship between efficiency measured by two different methods, Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA), and the profitability of banking financial institutions that operated in Brazil. We analyzed 47 banking financial institutions that operated in Brazil between 2008 and 2015. Institutional efficiency was measured using the Data Envelopment Analysis (DEA) and the Stochastic Frontier Analysis (SFA) methodologies, based on the indicators, which were calculated considering the approach of financial intermediation in order to measure the cost efficiency of financial institutions. Secondly, the scores found for the application of the DEA and of the SFA were related to the ROA (Return on Assets) and the ROE (Return on Equity) indicators of banking institutions, using the regression model with panel data. Through this analysis, a statistically significant relationship between efficiency and profitability of bank financial institutions was identified. The measures of profitability are related directly and significantly to the efficiency measured by the Data Envelopment Analysis (DEA) and the Stochastic Frontier Analysis (SFA) methods. In the managerial aspect, the results obtained show that efficiency is associated with profitability, with a greater influence on the ROE (Return on Equity) than on the ROA (Return on Assets) indicator. It was clear that efficiency has a significant impact on the return on the total of assets applied, but the impact is even greater on the return on equity invested in the banking financial institutions. Therefore, efficiency becomes even more relevant when the management objective is to maximize shareholder value. Thus, it is observed that studying the aspects related to the efficiency of banking institutions assumes an increasing relevance in the current Brazilian economic scenario of instability and high interest rates practiced by the banks.